The Influence of Applying a Teacher's Code of Ethics to Discipline in Teaching at SMK Parulian 1 Medan - Rita Dialusi Gultom; Hasyim; Elisabeth Manik (Indonesian Journal of Advanced Research, 2023)
This study aims to see the effect of applying a teacher's code of ethics on discipline in teaching at SMK Parulian 1 Medan. The sample in this study were 30 students at SMK Parulian 1 Medan with a non-probability sampling technique with purposive sampling. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is the one-sample t-test. The results showed that the application of the teacher's code of ethics at Parullian 1 Medan Vocational High School was good in terms of the average sample measurement score showing no change, teaching discipline in Parullian 1 Medan Vocational School was good in terms of the average sample measurement score showing no change.